2012
DOI: 10.1159/000336148
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Ventricular Arrhythmias after Myocardial Infarction with Diabetes Associated with Sympathetic Neural Remodeling in Rabbits

Abstract: Background: Abnormal sympathetic innervation underlies both long-term hyperglycemia and myocardial infarction (MI). The incidence of ventricular arrhythmias (VAs) after MI is higher in diabetic than in nondiabetic patients. However, the exact mechanism remains unclear. In this study, we aimed to explore sympathetic neural remodeling after MI in diabetic rabbits and its relationship with VAs. Methods: Rabbits were randomly assigned to 4 groups: control, diabetes mellitus (DM), MI and diabetic myocardial infarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…One potential explanation may be the increased susceptibility to VAs and sudden cardiac death [30]. Vinik and Ziegler [31] reported that autonomic neuropathy causes arrhythmias in diabetic individuals that are more severe than in normal individuals.Other studies have found that the QT interval is significantly prolonged in DM individuals compared to in normal individuals, which may be related to the incidence of VAs in these subjects [8,9]. In our study, after 28 weeks of DM, we observed a significant increase in inducible VAs in STZ-D rats, and the QTc and QTcd were more prolonged in the DS group than in the control group, which is consistent with previous results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One potential explanation may be the increased susceptibility to VAs and sudden cardiac death [30]. Vinik and Ziegler [31] reported that autonomic neuropathy causes arrhythmias in diabetic individuals that are more severe than in normal individuals.Other studies have found that the QT interval is significantly prolonged in DM individuals compared to in normal individuals, which may be related to the incidence of VAs in these subjects [8,9]. In our study, after 28 weeks of DM, we observed a significant increase in inducible VAs in STZ-D rats, and the QTc and QTcd were more prolonged in the DS group than in the control group, which is consistent with previous results.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have demonstrated that a prolonged QT interval and an increased incidence of VAs occur in diabetic individuals with CAN [8,9]. As has been demonstrated in previous studies [9,10,11,12], asymmetrical cardiac sympathetic innervation may contribute to the increased incidence of VAs. Heterogenous cardiac sympathetic innervation has also been observed in DM with CAN.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous studies have demonstrated that heterogeneous cardiac nerve sprouting and sympathetic hyperinnervation play important roles in arrhythmogenesis in both patients and animal models of MI [1,2,3,4]. Excess sympathetic innervation increases automaticity, triggers activity and creates spatial dispersion of refractoriness, which exacerbates electrophysiological heterogeneity and leads to a higher risk of ventricular arrhythmias and sudden cardiac death after MI [5].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bourke et al [8] reported a group of 14 patients with frequent ventricular tachycardia refractory to antiarrhythmic drugs and ablation procedures who underwent neuroaxial modulation through left cardiac sympathetic denervation. This study showed that in this patient population, left cardiac sympathetic denervation resulted In this issue of Cardiology , Wang et al [1] report the effects of myocardial infarction and hyperglycemia on cardiac sympathetic nerve remodeling in rabbits. The authors studied the structural and functional effects of such remodeling, including its electrophysiological properties and propensity for ventricular arrhythmias.…”
mentioning
confidence: 79%